Regenerative Medicine Ethics Governing Research and Knowledge Practices - Hogle, Linda F. (Springer New York : Imprint: Springer, 2014)
Regenerative medicine is at a pivotal point. Innovations in the science and the rapid growth of translational medicine are transforming the field just as institutional arrangements are changing, making this an exciting yet unsettled time. Recent court cases and policy initiatives are creating crosscurrents that keep older issues from being settled while introducing new dilemmas. Current research propels collaborations across disciplines and sectors, raising the question of how tensions between the protection of intellectual property and the movement toward 'open science' can be negotiated. Other important social, ethical and legal questions arise in the gray areas created by new scientific techniques and pragmatic areas involved in scale-up and testing in humans. The times call for governance that is adaptive to meet the needs of science yet able to maintain public trust.    The contributors address these and other vital questions through chapters focusing on topics such as data sharing; patenting of human biological material; and managing collaborations across academic, industry and government sectors as well as across national boundaries. Key research ethics issues are also included such as obtaining consent from biospecimen donors; accessing biorepository data, and considerations in designing preclinical and clinical trial protocols for first-in-human research, including upcoming policy changes.   Rather than retracing well-trodden topics, the book points to nascent areas that need to be addressed.  Whether working in academia, industry, or government, regenerative medicine scientists and managers need to know how to navigate current and upcoming issues of governance facing the field. Regenerative Medicine Ethics: Governing Research and Knowledge Practices will be a valuable resource for scientists, policy-makers and students as they plan and execute responsible research.    About the Editor     Linda F. Hogle is Professor of Medical Social Sciences in the School of Medicine & Public Health at the University of Wisconsin-Madison and Fellow at the Wisconsin Institutes for Discovery.  Her research includes analyses of social, ethical, and legal issues in emerging cell-based and biomedical engineering technologies, as well as concepts of risk in innovative science as understood by governance bodies. She has served as an advisor to several international research consortia focusing on stem cell and regenerative medicine.